Postoperative Alcohol Withdrawal Syndrome and Neuropsychological Disorder in Patients after Head and Neck Cancer Ablation Followed by Microsurgical Free Tissue Transfer - Chang, Chang-Cheng; Kao, Huang-Kai; Huang, Jung-Ju; Tsao, Chung-Kan; Cheng, Ming-Huei; Wei, Fu-Chan (Journal of Reconstructive Microsurgery, 2013)
Purpose The use of microsurgical free flap reconstruction has resulted in improved patient outcomes and survival after head and neck cancer resection. Although postoperative care in an intensive care unit (ICU) for airway management and flap surveillance can increase the success rate, any accompanying neuropsychological problems can potentially affect the outcome.Materials and Methods From January 2006 to December 2008, we retrospectively reviewed 1,506 ICU patients who underwent head and neck cancer ablative surgery followed by microsurgical free tissue transfer. Twelve patients (Group A) had alcohol withdrawal syndrome (AWS), whereas 29 patients (Group B) had other neuropsychological problems. The clinical manifestations and outcomes of each group were investigated and statically analyzed.Results All the flaps survived. There was no significant difference in onset time, duration, ICU stay, hospital stay interval, overall complications, and flap circulation-related complications. However, the non–flap-related complication rates (10/12, 83.3%; 14/29, 48.3%; p = 0.038), including failure of extubation or ventilator weaning (7/12, 58.3%; 7/29, 24.1%; p = 0.036), were significantly higher in Group A.Conclusion Patients with postoperative AWS have a higher chance of developing non–flap-related complications, especially respiratory problems. The identification of a multidisciplinary approach to identify and manage these patients preoperatively and postoperatively is required.
Keywords: head and neck cancer; microvascular surgery; alcohol withdrawal syndrome